การผลิตแพตตี้ปลาดุกบิ๊กอุยเสริมว่านหางจระเข้ - สมพงษ์ วรางคณา; จิตรหนัก จักรพงศ์; ปิ่นเย็น หฤษฎ์; สุดเลิศ ภัทิรา (Thai Journal of Science and Technology, 2018)
Abstract The objective of this study was to produce Hybrid Catfish Patties with Aloe vera. The optimum concentration of Aloe vera gel was studied by varying the weight ratio of Aloe vera gel to water at four levels: 0 : 100 (control), 50 : 50, 75 : 25 and 100 : 0. The results showed that patties with 50 % Aloe vera gel was similar to that with the control in % cooking loss and % juiciness. Moreover, sensory scores in taste, juiciness and overall liking did not show significantly different from that of the control. Then, texture improvement was conducted by varying types and concentrations of binders including wheat flour and soy protein isolate (SPI) at 2, 4 and 6 % by total weight. Catfish patties with 2 % SPI showed the high values in hardness, cohesiveness and chewiness, and exhibited the highest scores in appearance, flavor, firmness and overall liking. Shelf life studying at 4±2 °C for 6 days of cooked patties with Aloe vera and 2 % SPI and control formula showed that thiobarbituric acid value of control formula increased higher than that of formula with Aloe vera when storage time was prolonged. Based on the total viable count, it was noted that both formulas had shelf life at least 3 days. Proximate analysis indicated that patties with Aloe vera had significantly higher protein and fiber content than that of the control. Keywords: patties; hybrid catfish; Aloe vera; cooking loss; juiciness